2021
DOI: 10.1111/2041-210x.13598
|View full text |Cite
|
Sign up to set email alerts
|

What is our power to detect device effects in animal tracking studies?

Abstract: The use of bio‐logging devices to track animal movement continues to grow as technological advances and device miniaturisation allow researchers to study animal behaviour in unprecedented detail. Balanced against the remarkable data that bio‐loggers can provide is a need to understand the impact of devices on animal behaviour and welfare. Recent meta‐analyses have demonstrated the impacts of device attachment on animal behaviour, but there is a concern about the frequency and clarity with which device effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Recently, a few papers have pointed out the importance of quantifying the Type M and S error rates (Cleasby et al, 2021;Lemoine et al, 2016;. For example, Lemoine et al (2016) showed that reported effect sizes of global warming on plant and non-manipulative observations had very similar results in terms of their power, Type M and S errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a few papers have pointed out the importance of quantifying the Type M and S error rates (Cleasby et al, 2021;Lemoine et al, 2016;. For example, Lemoine et al (2016) showed that reported effect sizes of global warming on plant and non-manipulative observations had very similar results in terms of their power, Type M and S errors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few papers have pointed out the importance of quantifying the Type M and S error rates (Cleasby et al, 2021 ; Lemoine et al, 2016 ; T. H Parker et al, 2018 ). For example, Lemoine et al ( 2016 ) showed that reported effect sizes of global warming on plant growth were, on average, three times larger than a “true” effect that was approximated by an overall meta‐analytic mean (Type M error rate: 3).…”
Section: Introductionmentioning
confidence: 99%
“…We found a negative effect on beaver body weight change during the tagging period, but with considerable individual variation amongst tagged individuals. These findings might have implications regarding animal welfare and the validity of data collected [ 103 , 104 ]. The large variation among tagged beavers illustrates how effects of tagging should not only be studied by comparing averages among tagged and untagged individuals, but also by analyzing individual impacts.…”
Section: Discussionmentioning
confidence: 99%
“…3.2%). Despite these considerations, we acknowledge that negative effects remain difficult to detect, control and quantify and could still lead to behavioural ano malies ( Vandenabeele et al 2014, Cleasby et al 2021.…”
Section: Data Collectionmentioning
confidence: 99%